Psikologi lintas budaya / Sarlito W. Sarwono; Penyunting, Eko A. Meinarno dan Lathifah Hanum - SARLITO W. Sarwono; EKO A. Meinarno; LATHIFAH Hanum (Raja Grafindo Persada, 2014)
x, 188 hlm. : ilus. ; 23 cm.